2018
DOI: 10.1002/ecy.2438
|View full text |Cite
|
Sign up to set email alerts
|

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure

Abstract: Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long-term counts of breeding bird species that were detected at least once on islands in a land-bridge island system, and employed multi-species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 47 publications
(93 reference statements)
0
35
0
Order By: Relevance
“…Low occupancy probability has been examined broadly in single‐species studies, where precision in parameter estimates from single‐species models declines non‐linearly with decreasing occupancy (MacKenzie & Royle, ). In a multi‐species context, however, low average occupancy has been observed as a phenomenon, particularly when combined with low average detectability (Si et al, ), but it has been otherwise little explored. Guillera‐Arroita et al () explored two scenarios of MSOM performance with low average occupancy (0.27 and 0.13) but did not contrast these scenarios to those others with higher or lower occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…Low occupancy probability has been examined broadly in single‐species studies, where precision in parameter estimates from single‐species models declines non‐linearly with decreasing occupancy (MacKenzie & Royle, ). In a multi‐species context, however, low average occupancy has been observed as a phenomenon, particularly when combined with low average detectability (Si et al, ), but it has been otherwise little explored. Guillera‐Arroita et al () explored two scenarios of MSOM performance with low average occupancy (0.27 and 0.13) but did not contrast these scenarios to those others with higher or lower occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that although historical mechanisms, such as niche conservatism could help explain elevational diversity gradients of Himalayan birds (e.g., Wiens & Graham, ; Price et al, ), ecological processes still play an important role in shaping gradients of richness in this study, given the multiple families in each guild. Some degree of care is required when interpreting our results, because our line‐transect surveys may underestimate rare, or secretive species living in dense forests due to imperfect detection, and thus affect our observed biodiversity patterns (MacKenzie et al, ; Si et al, ). In our study, the problem of imperfect detection may be more likely to occur in areas of low and mid‐elevations as dense forests were often found in such areas (Wu, ), so that future studies may wish to allocate more survey efforts to these areas, or improve the sampling design to target rare species (Specht et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found the hump-shaped patterns of elevational diversity gradients are generally congruence across bird guilds that peaked at different elevation bands and were explained by divergent spatial and environmental factors. In practice, however, the same patterns could also be driven by other processes, such as historical imprints, instead of ecological limits to diversity (Wiens, 2011 Si et al, 2018). In our study, the problem of imperfect detection may be more likely to occur in areas of low and mid-elevations as dense forests were often found in such areas (Wu, 1983(Wu, -1987, so that future studies may wish to allocate more survey efforts to these areas, or improve the sampling design to target rare species (Specht et al, 2017).…”
Section: Caveats and Limitationsmentioning
confidence: 99%
“…We defined the areas within a radius of 1 km at each counting point as observation areas, and these areas were not overlapping to avoid double counting. The relatively small areas and clear boundaries of the wetlands guaranteed good detection of waterbirds, which is important when quantifying assemblage structures (Si et al, ).…”
Section: Methodsmentioning
confidence: 99%